Transnational terrorism and restrictive immigration policies - Marc Helbling; Daniel Meierrieks (Journal of Peace Research, 2020)
We investigate the relationship between transnational terrorism and the restrictiveness of immigration policies. We argue that transnational terrorism may create incentives for governments to implement more restrictive migration policies. First, more restrictive policies may make terrorism a more costly endeavor, discouraging future terrorist activity. Second, voters may hold the government accountable for the increased insecurity and economic instability terrorism produces; more restrictive migration policies may signal political resolve and meet public demand for security-providing policies, consequently reducing the government's chances of electoral defeat. We provide an empirical analysis of the effect of transnational terrorism on migration policy restrictiveness for a sample of 30 OECD countries between 1980 and 2010. We find that a greater exposure to transnational terrorism is associated with stricter migration controls, but not stricter migration regulations regarding eligibility criteria and conditions. This finding is robust to different model specifications, estimation methods, operationalizations of terrorism, and instrumental-variable approaches. It points to the securitization of immigration, providing partial support for the notion that transnational terrorism incentivizes migration policy change towards greater restrictiveness. However, the policy response appears to be surgical (affecting only migration controls) rather than sweeping (and thus not influencing broader migration regulations) for the countries in our sample.
Keywords: 330; immigration; immigration policy; securitization; transnational terrorism